(untitled) (Acta Scientiarum. Language and Culture, 2017)
This paper shares the results of a study into the way Iranian TEF or TEFAQ candidates treat the listening comprehension as a skill as well as their awareness and exploitation of metacognitive strategies while listening to an audio document. A Persian translation of the Metacognitive Awareness Listening Questionnaire (MALQ) was used in addition to another questionnaire specifically developed for this research in order to gage how important candidates think listening in L2 is compared to the other skills, how much time they spent on practicing listening, and how often they take advantage of authentic documents to improve their listening. Not only did the results show an underestimation of the listening comprehension skill by the majority of Iranian L2 learners, but they also pointed to significant differences in the way men and women exercised their ears and treated the incoming audio stream. The paper concludes that learners’ awareness of listening strategies needs to be raised through classroom instruction and frequent exploitation of authentic documents outside the classroom setting should be encouraged.